MODEL PEMBERDAYAAN KOMUNITAS NELAYAN BERBASIS UMKM UNIT PENGOLAHAN IKAN MELALUI BMT IAIN BENGKULU - Badaruddin Nurhab; Khairiyah El Wardah; Yunida Een Fryanti (Universitas Darussalam Gontor, 2021)
As one of the strategic steps that can be taken is to empower fishermen to not only utilize marine and fishery products for consumption, but how these products can be of use value that is more competitive and contributes to the economy in a sustainable manner. One of them is the fish processing-based MSME program. At present, BMT as a form of microfinance institution has two advantages. First, BMT is a baitul maal which one of the activities is in the form of raising and utilizing Zakat, Infaq and Shadaqah (ZIS) funds. The results of this research are in the Prosperous Fishermen Village of Bai Island, Bengkulu City, where most of the livelihoods of the community are fishermen, there is no management of marine products that have added value, such as making fish crackers, making fish shredded, or processed fish food such as nuget, fish balls or fish. the like. Seafood is directly sold at fish auctions or in traditional markets. This potential is very large to be developed through the assistance program of BMT Al-Muawannah IAIN Bengkulu to establish MSME Fish Processing Units so that they can provide added economic value that can help improve community welfare and develop maritime potential in Bengkulu.